PENGARUH CONTENT MARKETING DI INSTAGRAM STORIES @LCHEESEFACTORY TERHADAP MINAT BELI KONSUMEN - Amalia, Chairina Debika; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The development of content marketing encourages social media users to do marketing through the internet which focuses on creating and disseminating valuable, relevant and consistent content to attract and maintain a clearly defined audience, thus ultimately encouraging customers to take profitable actions. L’Cheese Factory using content marketing to promote its products through the Instagram Stories feature. The message which was published through the Instagram Stories feature by the Instagram account @lcheesefactory, aims to promote its products in order to arise consumers to buy the products they’ve offered.The purpose of this study is to know how much the influence of content marketing on Instagram Stories @LcheeseFactory on consumer buying interest. The theory used in this research is the S-R theory. The method used is a quantitative explanatory method. Researchers collected data with questionnaires and documentation. The population in this study are all followers of the Instagram account @lcheesefactory, amount to 45,200 account. Researchers used a simple random sampling technique. To find out how much influence between X and Y variables, the researchers used simple linear regression analysis. Meanwhile, to process the questionnaire test data, researchers using the version 23 of the Statistic Product and Service Solution (SPSS) program.Based on the results of a simple linear regression for research on the influence of content marketing on Instagram Stories @ LcheeseFactory towards consumer buying interest, the regression coefficient values obtained in this study is Y = 9,457 + 0,651 X with a significance level of 0,000 less than α = 0.05. This means that there is an influence of content marketing on Instagram Stories @LcheeseFactory towards the consumer buying interest of 23.6% which is included in the weak category. This means that H1 is accepted and Ho is rejected.